EMERGING TRENDS IN LEADERSHIP AND ORGANIZATIONAL FACTORS AFFECTING LECTURER COMPETENCE: A SYSTEMATIC REVIEW - Ade Sofyan; Zakaria Syafei; Naf'an Tarihoran; Anis Fauzi; Suherman Priatna (Jurnal Abdisci, 2024)
This research aims to uncover problems about emerging leadership trends and organizational factors that can affect lecturer competence. The research method used to examine the problems that occur today is by using a literature review (literature review), which is to review various literature that discusses leadership and organization as well as lecturer competencies and survey research that aims to generalize to reveal organizational factors that can affect lecturer competence. The results of this study show that today's leadership trend is mandatory to have basic competencies including pedagogic, professional, personal and social. Meanwhile, organizational factors, namely leaders have: accountability, enthusiasm, encouragement to lecturers, anticipation of organizational dynamics that occur and giving rewards to lecturers who perform good work and sanctions against lecturers who make mistakes. The ability of a leader and creating a good organizational environment in his leadership will provide an increase in lecturer competence.